Evidence of early deglaciation (18 000 cal a bp) and a postglacial relative sea‐level curve from southern Karmøy, south‐west Norway. (23rd July 2019) - Vasskog, Kristian; Svendsen, John‐Inge; Mangerud, Jan; Agasøster Haaga, Kristian; Svean, Arve; Lunnan, Eva Maria
ABSTRACT: Based on six consistent radiocarbon dates from the isolation basins Grødheimsvatnet and Kringlemyr, we estimate a minimum deglaciation age for southern Karmøy, an island in outer Boknafjorden (south‐west Norway), of around 18 000 calibrated years before present (18k cal abp ). We use microscopic phytoplankton, macrofossils, lithostratigraphic evidence and X‐ray fluorescence data to identify the isolation contacts in the basins, and date them to 17.52–17.18k cal abp in Grødheimsvatnet [15.57 m above present mean sea level (MSL)] and 16.19–15.80k cal abp in Kringlemyr (11.99 m above MSL). Combining these data with previous studies, we construct a relative sea‐level (RSL) curve from 18k cal abp until the present, which is 3 ka longer than any previous RSL reconstruction from southern Norway. Following deglaciation, southern Karmøy has experienced a net emergence of around 16–19 m, although with significant RSL fluctuations. This includes two RSL minima well below present MSL around 13.8 and 10k cal abp, and two maxima that culminated around 5–7 m above MSL during the Younger Dryas and early to mid‐Holocene, respectively. Considering eustatic sea level and modelled gravitational deformation of the geoid, we estimate a net postglacial isostatic uplift of 120 m. © 2019 John Wiley & Sons, Ltd